2013
DOI: 10.1021/es401403p
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Polymer-Coated Metal-Oxide Nanoparticles and their Toxicological Effects on Zebrafish (Danio rerio) Development

Abstract: Coated nanoparticles (NPs) will end up in the environment due to their proposed use in agricultural applications and may potentially cause toxic effects due to their unique properties. To determine the effects of coated NPs on zebrafish (Danio rerio) development, we tested aqueous poly(acrylic acid) (PAA)-coated metal-oxide NPs including TiO2, ZnO, Fe2O3, and CeO2, as well as the polymer coating alone (nanocapsule). Zebrafish embryos were exposed to NPs over a 72 h period at 1, 10, 50, 100, 200, 400, 800, 1200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…the positive-charged quaternary ammonium groups binding to the host materials could present electrostatic interaction towards the target fluoride ions, leading to the enhanced sorption diffusion kinetics and fluoride ions enrichment, prior to sequestration by nano-ZrP, such phenomenon is the so-called “Donnan membrane effect”3839. Recent research also further proved that such polymer encapsulating metal nanoparticles could cause negligible toxic effects on organism in waters40. Besides, the excellent chemical stability and non-toxic properties of ZrP particles also render us believe that the hybrid nanomaterial ZrP-MPN is a promising adsorbent towards fluoride retention.…”
mentioning
confidence: 99%
“…the positive-charged quaternary ammonium groups binding to the host materials could present electrostatic interaction towards the target fluoride ions, leading to the enhanced sorption diffusion kinetics and fluoride ions enrichment, prior to sequestration by nano-ZrP, such phenomenon is the so-called “Donnan membrane effect”3839. Recent research also further proved that such polymer encapsulating metal nanoparticles could cause negligible toxic effects on organism in waters40. Besides, the excellent chemical stability and non-toxic properties of ZrP particles also render us believe that the hybrid nanomaterial ZrP-MPN is a promising adsorbent towards fluoride retention.…”
mentioning
confidence: 99%
“…Thus, ZnO may attract more PAA than TiO 2 , for example, and form thicker polymer coats that could mask adverse core material‐mediated effects such as toxicity. The effects on viability were likely not related to the release of core metal ions as the dissolution of PAA‐NPs have not been demonstrated in ultrapure water,10 or in simulated biological solutions 23. As well, viability did not decrease over 24 h when RBL‐2H3 cells were exposed to Ti, Zn, Fe, and Ce ions (data not shown) at dialyzed concentrations previously determined for PAA‐NPs 10…”
Section: Discussionmentioning
confidence: 69%
“…Given that the primary particle diameters of the PAA‐NPs tested in this study are between 3 and 10 nm10, 22 and have high negative charge,22 we investigated the hypothesis that these smaller materials may still bind FcεRI and sterically obstruct IgE from properly attaching to the receptor and therefore inhibit the degranulatory response. Our data showed that cells pre‐exposed to PAA‐TiO 2 had significant reductions in IgE binding, relative to control, suggesting that PAA‐TiO 2 altered the attachment of IgE to FcεRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, dissolution analysis was performed in ultrapure water whereas dissolution will likely be greater at the higher ionic strength of the tap water used in the experiments and also likely in the high ionic strength environment of chorionic fluid where nanoscale materials have been observed. [173] Moreover, the study of Ong et al [47] is one of very few to directly compare the toxicity of uncoated and coated NMs where they found minor effects on hatch in embryos exposed to polyacrylic acid stabilised ZnO NMs, further suggesting that Zn 2þ dissolution dominates as the source of hatch impairment and therefore it is difficult to define the role of colloidal NM interaction with the hatching enzyme in Zn 2þ -containing NMs. [47] Although the role of released Zn 2þ towards toxicity has not been fully resolved, Zn 2þ appears to have greater bioavailability than nanoscale ZnO.…”
Section: Zinc Oxide Nmsmentioning
confidence: 99%